Postoperative analgesic efficacy of caudal dexamethasone added to bupivacaine vs bupivacaine alone for pediatric elective infra-umbilical surgery at (Tikur Anbesa Specialized Hospital), Ethiopia: Prospective cohort study. (2020) - Gashaw, Amanu; Dendir, Getahun; sitot, Mulualem; Balcha, Bahailu; Aweke, Zemedu
Abstract: Background: Caudal block is the most preferred technique of postoperative analgesia in pediatrics, despite its limited duration of action. Many additives are used to improve the efficacy of caudal blocks, such as opioids or α2 agonists. Recently, there has been increased use of caudal dexamethasone as postoperative analgesia. Objective: To assess the efficacy of adding caudal dexamethasone on bupivacaine for postoperative analgesia in pediatric infra-umbilical surgery. Method: A prospective cohort study design was employed for two equal groups of 30 children aged 1–14 years scheduled for infra-umbilical surgery under caudal bupivacaine; those exposed to dexamethasone (BD) were considered to be the exposed group and those exposed to bupivacaine alone (B) were the non-exposed group. Pain severity, first analgesia request time as well as analgesic consumption were assessed using Mann-Whitney U test for 24 h. Chi-square test was used to analyze the homogenous categorical independent variables between these two groups and a p-value less than 0.05 was considered to be statistically significant. Result: The dexamethasone with bupivacaine group had significant prolonged postoperative analgesia with a median of 915 (650–1, 440) minutes compared with 433 (328–555) minutes in the bupivacaine-alone group (p < 0.001). Moreover, the total analgesic consumption was significantly lower in the dexamethasone group with a median total dose of 55 (0–250) mg compared with 402 (95–812) mg in the bupivacaine group with (p < 0.001). Pain score in the dexamethasone group was reduced, being statically significant at 4th, 8th and 12th hrs. Conclusion: Dexamethasone with bupivacaine decreases postoperative pain severity and total analgesic consumption and prolongs the duration of analgesia. Therefore, we recommend the use of caudal dexamethasone with bupivacaine as an effective option for postoperative analgesia. Highlights: Administering caudal dexamethasone with bupivacaine significantly prolongs postoperative analgesia. Consumption of analgesic was significantly lower with the usage of caudal dexamethasone with bupivacain. Extensive lower pain score was observed in caudal dexamethasone bupivacaine group compared to caudal bupivacaine alone. Vital signs before and after skin incision and immediately post anesthesia care units were similar in both groups. Nausea and vomiting reduces highly caudal dexamethasone with bupivacaine group compared with caudal bupivacaine alone.